Training on Corn-Based Healthy Nugget Innovation for BUMDes Kebontunggul - Zenita Afifah Fitriyani; Oktaviani Permatasari; Nurus Sabani; Harjo Lukito; Buyung Cahya Perdana (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service activity aimed to improve the knowledge and practical skills of BUMDes Kebontunggul administrators and members in processing corn into healthy nuggets as an innovative local food product with added value. Method: The activity was conducted at Kebontunggul Village Hall through three stages: preparation, implementation, and evaluation. The preparation stage included observation, coordination with BUMDes managers, and identification of local potential and partner needs. The implementation stage consisted of material delivery on corn value addition, healthy corn-based nugget formulation, and business opportunities, followed by hands-on practice in preparing and processing the product. The evaluation stage was carried out through observation of participation and assessment of participants’ understanding and practical involvement during the training. Practical Applications: The activity showed that participants improved their understanding of corn processing as a value-added product, were able to follow the stages of making healthy corn-based nuggets, and gained broader insight into the potential development of local food-based business initiatives within the BUMDes environment. Conclusion: This activity contributed to strengthening community capacity in local food diversification, increasing awareness of healthy food innovation, and supporting the initial development of corn-based products as a potential BUMDes business initiative.